Perception of Ease and Herding Behavior: The Role of Knowledge in Investment Decisions on Gold Among the Youth in Serang City - Muti’ah Nurul Jannah; Suryani Suryani; Syaeful Bahri (Eduvest - Journal of Universal Studies, 2026)
The surge in gold prices has given rise to the phenomenon of the gold rush among the younger generation. Technological advancements have increased the ease with which the younger generation can invest in gold, while the fear of missing out (FOMO) can foster herding behavior in gold investment decisions. This study aims to analyze the influence of perceived ease, herding behavior, and the level of investment knowledge on gold investment decisions. It also aims to examine investment knowledge as a moderating variable. The quantitative approach employed in this research uses Partial Least Squares Structural Equation Modeling (PLS-SEM) with random sampling techniques. The findings indicate that investment knowledge has a positive and significant impact on investment decision-making. In addition, the perception of ease has been proven not only to enhance investment knowledge but also to directly drive investment decisions. Meanwhile, herding behavior does not show a significant influence on either investment knowledge or investment decisions. The study also reveals that investment knowledge does not function as a moderating variable in the relationship between herding behavior, perceived ease, and investment decisions.